THEMATIC PROGRESSION ANALYSIS OF STUDENTS WRITING - Trisnendri Syahrizal; Leilani Syahrizal; Nida Anggraeni (LP2M-PMP Universitas Siliwangi, 2018)
Thematic progression is a way of developing themes and rhemes in clauses. In other words, thematic progression is a strategy or a specific way to make writing more effective. In addition, thematic progression is a prominent aspect of systemic linguistic functional. Thematic progression has been widely studied in English over the past few years and proves that is very important element in writing. In other words, good writing is effective writing. Therefore, themes and rhemes play a role in creating good texts. Besides that, thematic progression has also been done for many purposes. Therefore, the focus in this study is to describe the pattern of thematic progression in a student writing. It purpose to know which thematic pattern of progression is widely used in the student's writing. Therefore, this research entitled Thematic Progression Analysis in Students' Writing. In this study the researchers used the theory of Bloor and Bloor (2014) which states there are 4 types of patterns of thematic progression, namely the constant theme pattern, the linear theme pattern, the split theme pattern, and the derived theme pattern. To carry out this research, the data is taken from the writings of English A2 / 2014 students in IKIP Siliwangi, Cimahi. There are 47 student writing data. The researcher took 5 samples from the data by choosing the same number of sentences from each text. The results show that the thematic development pattern that is widely used by the students of class A2 / 2014 is the pattern of constant theme, the second pattern is linear theme, the third pattern is the split theme and the last pattern is the derived theme.